Perspektif Asas Keadilan Terhadap Pekerja/Buruh yang di Putus Hubungan Kerja (PHK) yang diatur dalam Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja Jo Peraturan Pemerintah Nomor 35 Tahun 2021 (Putusan Pengadilan Negeri Serang Nomor 3/Pdt.Sus-PHI/2018/PN.Srg dan Putusan Pengadilan Hubungan Industrial pada Pengadilan Negeri Serang Nomor 111/Pdt.Sus-PHI/2021/PN.Srg) - Pandri Zulfikar; Saparudin Saparudin (ARBITER: Jurnal Ilmiah Magister Hukum, 2022)
This article aims to find a fair view of workers/labourers regarding the value of severance pay when workers are affected by Termination of Employment (PHK) which has been regulated in Law Number 1 of 2020 concerning Job Creation in conjunction with Government Regulation Number 35 of 2021. Linked to Court Decisions Serang District Number 3/Pdt.Sus-PHI/2018/PN.Srg and the Decision of the Industrial Relations Court at the Serang District Court Number 111/Pdt.Sus-PHI/2021/PN.Srg. The purpose of this study is how to regulate laid-off workers/labourers in terms of providing severance pay, service pay and compensation in Law Number 11 of 2020 concerning Job Creation which has been regulated in Law Number 1 of 2020 concerning Job Creation. Government Regulation Number 35 of 2021. Relates to the Serang District Court Decision Number 3/Pdt.Sus-PHI/2018/PN.Srg and the Industrial Relations Court Decision at the Serang District Court Number 111/Pdt.Sus-PHI/2021/PN.Srg realize the principle of justice to Workers/Labourers. The research method used is empirical normative juridical with primary and secondary data. Research results Efforts to realize the principle of justice regarding the provision of severance pay, service pay and compensation in Law Number 11 of 2020 concerning Job Creation is to revise Article 156 paragraph (1) and paragraph (4) of Law Number 11 Year 2020 regarding Job Creation in conjunction with Government Regulation Number 35 of 2021 Work Agreements for Specific Time, Outsourcing, Working Time and Rest Time, and Termination of Employment. by involving the participation of Trade Unions and employers.